Myelopathy due to ossification or calcification of the ligamentum flavum: radiologic and histologic evaluations. - Miyasaka, K; Kaneda, K; Sato, S; Iwasaki, Y; Abe, S; Takei, H; Tsuru, M; Tashiro, K; Abe, H; Fujioka, Y (American Journal of Neuroradiology, 1983)
The clinical, radiologic, and histologic features of ossification and calcification of the ligamentum flavum were studied in 18 patients. Ossification (15 patients) usually occurred in the lower thoracic spine in men of various ages, while calcification (three patients) was found exclusively in the cervical region of older women. Histologic examinations of ossification showed mature lamellar bone associated with proliferated cartilage replacing the ligamentum flavum (endochondral ossification). This corresponded well with radiographic and computed tomographic (CT) appearances. In the cases with calcification of the ligamentum flavum, calcification within the degenerated ligamentous fibers was observed on histologic examination, and correlated well with an oval nodular density on radiographs and CT. The two conditions differ in clinical, radiologic, and histologic considerations. Pathomechanisms in the development of these lesions and clinical significance are also discussed.